TFG, a target of chromosome translocations in lymphoma and soft tissue tumors, fuses to GPR128 in healthy individuals - Chase, Andrew; Ernst, Thomas; Fiebig, Andreas; Collins, Andrew; Grand, Francis; Erben, Philipp; Reiter, Andreas; Schreiber, Stefan; Cross, Nicholas C. P. (Haematologica, the hematology journal, 2010)
BACKGROUND: The formation of fusion genes plays roles in both oncogenesis and evolution by facilitating the acquisition of novel functions. Here we describe the first example of a human polymorphic in-frame fusion of two unrelated genes associated with a copy number variant. - DESIGN AND METHODS: Array comparative genomic hybridization was used to identify cryptic oncogenic fusion genes. Fusion gene structure and origin was examined using molecular biological and computational methods. Phenotype associations were examined using PopGen cohorts. - RESULTS: Targeted array comparative genomic hybridization to identify cryptic oncogenic fusion genes in patients with atypical myeloproliferative neoplasms identified a 111 kb amplification with breakpoints within the TRK-fused gene (TFG, a target of translocations in lymphoma and thyroid tumors) and G-protein-coupled receptor 128 (GPR128) resulting in an expressed in-frame TFG-GPR128 fusion transcript. The fusion gene was also identified in healthy individuals at a frequency of 0.02 (3/120). Normally both genes are in identical orientations with TFG immediately downstream of GPR128. In individuals with a copy number variant amplification, one or two copies of the TFG-GPR128 fusion are found between the two parental genes. The breakpoints share a region of microhomology, and haplotype and microsatellite analysis indicate a single ancestral origin. Analysis of PopGen cohorts showed no obvious phenotype association. An in silico search of EST databases found no other copy number variant amplification-associated fusion transcripts, suggesting that this is an uncommon event. Conclusions The finding of a polymorphic gene fusion in healthy individuals adds another layer to the complexity of human genome variation and emphasizes the importance of careful discrimination of oncogenic changes found in tumor samples from non-pathogenic normal variation.
Gesehen am 17.02.2023